Case Report: Noncomitant Ocular Deviation - Pace, Rodger (Canadian Journal of Optometry, 1982)
The optometrist is often called upon to diagnose and manage the patient with noncomitant ocular deviations. A case of noncomitant phoria is described with emphasis on the Parks 3-step method for identifying the involved muscle. Patient management is discussed.